A heuristic algorithm searching optimum routes for maritime transportation. (2016) - Chainas, Konstantinos
The present essay presents a heuristic algorithm for the optimisation of coastal vessel's routes. The task is to research the optimum connection between two ports, incorporating in their routes intermediate nodes, which must satisfy certain limitations and some preconditions related to total distance, trip duration, and demand coverage. This issue has many common elements with the overall vehicle routing problem and the team orienteering problem, but, at the same time, presents with significant particularities. Its particularities consist mainly in the fact that in the sea area, each node may be theoretically linked to any other node, without limitations, while a road network has a specific structure. The results of the algorithm implementation for its region of application were improved compared to that in the literature. The advantages of its application by the maritime companies for the search of the optimal itineraries will be important mainly in terms of resource saving.